2011
DOI: 10.1002/eat.20939
|View full text |Cite
|
Sign up to set email alerts
|

Childhood emotional abuse and eating symptoms in bulimic disorders: An examination of possible mediating variables

Abstract: We found CEA to predict eating pathology through mediating effects of ineffectiveness and affective instability. CEA might influence severity of ED symptoms by impacting an individual's self-esteem and capacity for affect regulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
38
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(46 citation statements)
references
References 35 publications
7
38
0
1
Order By: Relevance
“…Interrater reliability estimates were calculated for each type of abuse in a selected sample of CTI interviews (N ¼ 49), revealing k ¼ 0.77 for emotional abuse, k ¼ 0.84 for physical abuse and k ¼ 0.93 for sexual abuse. We note that such coding of abuse has been used in the past by our group (Groleau et al, 2012) and has yielded rates of abuse highly comparable to those published elsewhere (e.g., Rorty et al, 1994;Steiger et al, 2010). DAT1.…”
Section: Methodssupporting
confidence: 59%
See 1 more Smart Citation
“…Interrater reliability estimates were calculated for each type of abuse in a selected sample of CTI interviews (N ¼ 49), revealing k ¼ 0.77 for emotional abuse, k ¼ 0.84 for physical abuse and k ¼ 0.93 for sexual abuse. We note that such coding of abuse has been used in the past by our group (Groleau et al, 2012) and has yielded rates of abuse highly comparable to those published elsewhere (e.g., Rorty et al, 1994;Steiger et al, 2010). DAT1.…”
Section: Methodssupporting
confidence: 59%
“…For instance, childhood physical abuse (CPA) and childhood sexual abuse (CSA) have been associated with dissocial and impulsive traits in BN (Steiger et al, 2010), borderline personality disorder (Steiger et al, 1996), and submissiveness (Leonard et al, 2003). Moreover, recent reports suggest that childhood emotional abuse (CEA) is related to eating-disorder symptom severity, and to comorbid depression, affective instability, impulsivity and felt ineffectiveness (Kong and Bernstein, 2009;Groleau et al, 2012).…”
Section: Bn and Childhood Abusementioning
confidence: 99%
“…Clinical and preclinical studies have demonstrated that early-life adversity can increase vulnerability to eating disorders and dysfunctional feeding behavior (Groleau et al, 2012). Despite being a mild early-life experience with many positive effects on behavioral and physiological function, neonatal handling can significantly alter feeding behavior in rats (McIntosh, Anisman, & Merali, 1999; Silveira et al, 2008).…”
Section: Neonatal Handling and Food Consumptionmentioning
confidence: 99%
“…Some studies suggest greater EDs severity92223 in cases of physical and/or sexual abuse, whereas others do not48202425. Emotional abuse might also increase EDs severity6142627. Moreover, if child maltreatment is usually associated with a lower quality of life2829, to our knowledge, the impact of childhood abuse on quality of life and daily functioning in EDs remains completely unknown.…”
mentioning
confidence: 98%
“…Childhood abuse appears to be frequent in patients with binge episodes or impulsive characteristics45678. The findings on the association between childhood abuse and symptoms closely related to body concern, such as body dissatisfaction910 or drive for thinness11, have been more discrepant.…”
mentioning
confidence: 99%